Rotational Thromboelastometry and Its Use in Directing the Management of Coagulopathy in the Battle Injured Trauma Patient. Issue 1 (January 2014) - Benson, G
The military hospital at camp bastion Afghanistan is reputed to be the world's busiest trauma centre. Much has been learnt there in the field of managing massive haemorrhage, the protocols used by the military show a significantly higher survival rate than might be expected of such injuries. This article aims to explain the use of rotational thromboelastometry (ROTEM) monitoring and its role in reducing mortality in battle injured trauma patients.